2014
DOI: 10.1039/c4sm01728e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer fluctuation lubrication in hydrogel gemini interfaces

Abstract: Interfacial sliding speed and contact pressure between the sub-units of particulate soft matter assemblies can vary dramatically across systems and with dynamic conditions. By extension, frictional interactions between particles may play a key role in their assembly, global configuration, collective motion, and bulk material properties. For example, in tightly packed assemblies of microgels - colloidal microspheres made of hydrogel - particle stiffness controls the fragility of the glassy state formed by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 34 publications
8
75
1
Order By: Relevance
“…Gemini hydrogel interfaces can provide exceptionally low friction coefficients under conditions traditionally not thought to promote lubrication, namely, low contact pressure and low sliding speed [16,37]. In the series of experiments described here, the samples with the largest mesh size (ξ = 9.4 ± 1.1 nm) exhibited the lowest measured friction coefficients (µ ~ 0.005), and maintained this behavior over a range of sliding speeds from V s = 30-1,000 µm s -1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gemini hydrogel interfaces can provide exceptionally low friction coefficients under conditions traditionally not thought to promote lubrication, namely, low contact pressure and low sliding speed [16,37]. In the series of experiments described here, the samples with the largest mesh size (ξ = 9.4 ± 1.1 nm) exhibited the lowest measured friction coefficients (µ ~ 0.005), and maintained this behavior over a range of sliding speeds from V s = 30-1,000 µm s -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In previous work on Gemini hydrogel friction, we found that the lubrication curve differed dramatically from the classical engineering Stribeck curve in several major ways [16,37]. First, at slow sliding speeds, where the effects of hydrodynamic lubrication are negligible, Gemini hydrogel friction is actually lowest.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 3 more Smart Citations